PERAN GURU BIMBINGAN DAN KONSELING TERHADAP PENDIDIKAN KARAKTER SISWA DI SMAN TITIAN TERAS H. ABDURRAHMAN SAYOETI - Wina Gusey Nova Gulo; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Each student has unique characteristics. Throughout the learning process, SMAN Titian Teras H. Abdurrahman Sayoeti emphasizes character education, significantly supported by guidance and counseling teachers. This study aims to investigate the role of these teachers in shaping students' character at the school. A qualitative descriptive approach was used, with informants including the principal, vice principal for curriculum, the coordinator of guidance and counseling teachers, and four students. The data analysis process involved data collection, reduction, presentation, and conclusion drawing. The study found that guidance and counseling teachers play several key roles: identifying students' character needs, implementing programs, providing individual and group counseling, coordinating efforts, and conducting monitoring and evaluation. Challenges encountered include limited time and resources, communication with parents, students' psychological conditions, and managing large classroom settings.